TGF-Beta Receptor II Is Critical for Osteogenic Progenitor Cell Proliferation and Differentiation During Postnatal Alveolar Bone Formation - Xu, Chunmei; Xie, Xudong; Zhao, Hu; Wu, Yafei; Wang, Jun; Feng, Jian Q. (Frontiers in Physiology, 2021)
It is well-known that transforming growth factor beta (TGFb) signaling enhances osteogenesis. Most researches toward bone biology center on cortical and trabecular bone, while the alveolar bone is often overlooked. To address the role of Tgfbr2 (the most critical receptor for TGFb signaling) during postnatal alveolar development, we conditionally deleted Tgfbr2 in early mesenchymal progenitors by crossing Gli1-CreERT2; Tgfbr2fl/fl; and R26RtdTomato (for cell lineage tracing; named early cKO) or in mature osteoblasts by crossing 3.2kb Col1-CreERT2; Tgfbr2fl/f; R26RtdTomato (named late cKO). Both cKO lines were induced at postnatal day 5 (P5) and harvested at P28. Compared to the control littermates, the early cKO mice exhibited significant reduction in alveolar bone mass and bone mineral density with a drastic defect in periodontal ligament (PDL) cells, although the late cKO alveolar bone displayed a very minor phenotype. Further mechanism studies showed a significant reduction in PCNA+ PDL cell numbers and OSX+ cell numbers, as well as the disorganized distribution of PDL fibers with a great reduction of PERIOSTIN (the most abundant extracellular matrix protein) at levels of both mRNA and protein. We also found an interesting impact of TGFb on Wnt-b-catenin signaling as below: a drastic reduction in b-catenin in the early cKO PDL and a great increase in SOST (a potent inhibitor of Wnt signaling). Ironically, there was a very minor change in long bone of cKO mice. Together, we conclude that Tgfbr2 plays a critical role during early alveolar bone formation via promoting PDL cell proliferation and differentiation mechanisms.